Makanan Adat Pada Acara Perkawinan Di Desa Lubuk Kembang Kabupaten Rejang Lebong Bengkulu - Istiqomah, Tia; Baidar, Baidar; Fridayati, Lucy (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This research is grounded of the society are still trying to bequeath the tradition only by mouth to mouth, so they are worried the information would be defferent between each generation. The purpose of this research is to describe of how wedding ceremoni step by step, type of course that are being served, the type of recipe, and the food serving at the wedding ceremony in Lubuk Kembang village Rejang Lebong Bengkulu. Thr type of research is a qualitative research. The data colection technique is snowball sampling. The result of the research showing (1) The arangement of the wedding ceremony are the event before the ceremony, the main event, and after ceremony event. (2) As for the type of the course being served are staple food, side dish, vegetables, sambal, cakes and drinks. (3) The amount of the collected recipe are 21 recipe in total, consisting of 6 recipes of side dish, 5 recipes of vegetables, 4 recipe of sambal, 6 recipes of cakes. (4) The way of the event owner serving of the course is Jamuan Kutai.Keyword: The traditional food in the wedding ceremony